Heterogeneous ensembles for predicting survival of metastatic, castrate-resistant prostate cancer patients [version 3; referees: 1 approved, 2 approved with reservations] - Sebastian Pölsterl; Pankaj Gupta; Lichao Wang; Sailesh Conjeti; Amin Katouzian; Nassir Navab (F1000Research, 2017)
Ensemble methods have been successfully applied in a wide range of scenarios, including survival analysis. However, most ensemble models for survival analysis consist of models that all optimize the same loss function and do not fully utilize the diversity in available models. We propose heterogeneous survival ensembles that combine several survival models, each optimizing a different loss during training. We evaluated our proposed technique in the context of the Prostate Cancer DREAM Challenge, where the objective was to predict survival of patients with metastatic, castrate-resistant prostate cancer from patient records of four phase III clinical trials. Results demonstrate that a diverse set of survival models were preferred over a single model and that our heterogeneous ensemble of survival models outperformed all competing methods with respect to predicting the exact time of death in the Prostate Cancer DREAM Challenge.